AIMS FOR USING FUN GAMES TO IMPROVE THE ESL STUDENTS’ SPEAKING ABILITY - . Maisarah (Educate, 2014)
Maisarah Unipdu – Jombang Inmai5@yahoo.com Abstract This article reveals the reasons why fun games are effective to help the students improve their vocabularies and use the language actively. The use of games can be a good language learning tool. During the games, a student not only competes with other students to achieve the learning goal but also collaborates with the others. This process makes the students do the game as good as possible for the sake of winning. When the games are applied, the students are „forced‟ to speak and they will try to use vocabularies related to the theme of the game. It would be very helpful especially for the students in building their confidence and improving their speaking ability. Moreover, games can be used to help the students of beginning level through the silent period. They facilitate the students through many kinds of learning so that the ESL students can absorb the language very well. Not only the reasons to use fun games in the classroom, this article also shares how to choose suitable games for the students completed with their application in the classroom. Keywords: Fun games, ESL students, speaking ability